Silica Aerogel Improves the Biocompatibility in a Poly-ε-Caprolactone Composite Used as a Tissue Engineering Scaffold - Jianhua Ge; Musen Li; Qingguo Zhang; Christopher Z. Yang; Paul H. Wooley; Xiaofeng Chen; Shang-You Yang (International Journal of Polymer Science)
Poly-ε-caprolactone (PCL) is a biodegradable polyester that has received great attentions in clinical and biomedical applications as sutures, drug delivery tool, and implantable scaffold material. Silica aerogel is a material composed of SiO2 that has excellent physical properties for use in drug release formulations and biomaterials for tissue engineering. The current study addresses a composite of silica aerogel with PCL as a potential bone scaffold material for bone tissue engineering. The biocompatibility evaluation of this composite indicates that the presence of silica aerogel effectively prevented any cytotoxic effects of the PCL membrane during extended tissue culture periods and improved the survival, attachment, and growth of 3T3 cells and primary mouse osteoblastic cells. The beneficial effect of silica aerogel may be due to neutralization of the acidic condition that develops during PCL degradation. Specifically, it appears that silica aerogel to PCL wt/wt ratio at 0.5 : 1 maintains a constant pH environment for up to 4 weeks and provides a better environment for cell growth.